Sistema de Informação em Saúde para a análise de avaliações médicas - De Souza, Gabriel Spadon [UNESP]; Correia, Ronaldo Celso Messias [UNESP]; Garcia, Rogerio Eduardo [UNESP]; Olivete, Celso [UNESP]; Santos, Bruno Renan Gelako [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2016)
The process of data collection involves the organization of a group of questions, where its answers will be analyzed to obtain results. This process is faced with difficulty of standardization and obtaining accurate results, where usually the collect, storage and computation of results are manually realized. Several factors may cause unwanted results, like poorly completed forms, difficulty of interpretation of what was informed and disinterest of who fills it. Not all problems can be simply solved, but HIS (Health Information System) AIDS the process and data analysis, ensuring consistency and integrity. This work presents WebSISLapam, a web application to collect, organize and analyze data related to medical survey responses, supporting the creation and reuse of forms, questions and quantitative and qualitative variables.
Health information system for medical survey analysis
Keywords: e-Health; Health Information System (HIS); medical analysis; web system; WebSISLapam